دراسة قياسية للعلاقة بين معدل البطالة والنمو الاقتصادي في الجزائر خلال الفترة (1990-2013 ) باستخدام التكامل المشترك - صباح, زروخي; عبد الحميد, أ.د برحومة (Recherches économiques et managériales, 2014)
تهدف هذه الورقة إلى تحليل طبيعة العلاقة التي تربط معدلات البطالة بالنمو الاقتصادي في الجزائر خلال الفترة: 1990-2013، ومن اجل معرفة ما إذا كانت السلاسل الزمنية الخاصة بالمتغيرين مستقرة أم لا فقد تم استخدام اختبار جذر الوحدة، لفحصها والتأكد من مدى استقراريتها، حيث يتم تحديد رتبة كل متغير النتائج المتوصل إليها في الدراسة تبين أن متغيرات النموذج متكاملة من الدرجة الأولى، أما فيما يخص اختبار التكامل المشترك بين المتغيرين فقد أوضحت الدراسة عدم وجود تكامل مشترك بين المتغيرين محل الدراسة الكلمات الدالة: معدلات البطالة، النمو الاقتصادي، التكامل المشترك     Abstract This paper aims to analyze the nature of the relationship between unemployment rates and economic growth in Algeria during the period: 1990-2013, in order to see whether time series of the two variables were stable or not, it has been used unit root test, to examine and ascertain the extent stability so as to be able to identify the rank of each variable.       The results have shown that the variables formed an integrated first-class, but with regard to co-integration test between the two variables, this study has shown a lack of co-integration between the two variables of concern. Keywords : unemployment rates, economic growth, co-integration